Risk factors for hepatic hydrothorax in patients with cirrhosis: a clinical retrospective study - Bai, Xue; Liu, Xiaoyan; Shi, Yanhui; Li, Wenwen; Li, Qiang; Du, Wenjun (Frontiers in Medicine, 2023)
Abstract Aims & background: Hepatic hydrothorax, which presents as an unexplained pleural effusion, is one of the important complications in patients with end-stage cirrhosis. It has a significant correlation with prognosis and mortality. The aim of this clinical study was to detect the risk factors for hepatic hydrothorax in patients with cirrhosis and to better understand potentially life-threatening complications. Methods: Retrospectively, 978 cirrhotic patients who were hospitalized at the Shandong Public Health Clinical Center from 2013 to 2021 were involved in this study. They were divided into the observation group and the control group based on the presence of hepatic hydrothorax. The epidemiological, clinical, laboratory and radiological characteristics of the patients were collected and analyzed. ROC curves were used to evaluate the candidate model’s forecasting ability. Furthermore, 487 cases in the experimental group were divided into left, right, and bilateral groups and the data were analyzed. Results: The patients in the observation group had a higher proportion of upper gastrointestinal bleeding (UGIB), a history of spleen surgery, and a higher model for end-stage liver disease (MELD) scores compared with the control group. The width of the portal vein (PVW)(P=0.022), prothrombin activity (PTA)(P=0.012), D-Dimer (P=0.010), immunoglobin G (IgG)(P=0.007), high-density lipoprotein cholesterol (HDL)(P=0.022), and the MELD score were significantly associated with the occurrence of the hepatic hydrothorax. The AUC of the candidate model was 0.805 (P<0.001, 95% CI=0.758-0.851). Portal vein thrombosis was more common in bilateral pleural effusion compared with the left and right sides (P=0.018). Conclusion: The occurrence of hepatic hydrothorax has a close relationship with lower HDL, PTA, and higher PVW, D-Dimer, IgG, and MELD scores. Portal vein thrombosis is more common in cirrhotic patients with bilateral pleural effusion compared to those with unilateral pleural effusion.